Not that it Matters - Milne, A. A. (Alan Alexander), 1882-1956 (Salt Lake City, UT : Project Gutenberg, 2004)
"Not That it Matters" by A. A. Milne is a collection of essays written in the early 20th century. This work showcases Milne's witty observations on various subjects such as suburban life, the joys of writing, and the nature of golf, often blending humor and introspection. Through his reflections, Milne presents relatable anecdotes and humor that resonate with the everyday experiences of his readers. The opening of "Not That it Matters" introduces us to Milne's musings on writing. In a light-hearted manner, he discusses the pressure of producing written content, whimsically attributing his inspiration to the excitement of a new pen nib. This sets the tone for the book as he humorously navigates through different topics, such as suburban life on Acacia Road, where he imagines the intimacies of domestic life against the backdrop of a peaceful street. Milne smoothly transitions into reflections on his library and the motivations behind writing, revealing a playful yet thoughtful approach that invites readers into his world of charming observations and delightful prose. (This is an automatically generated summary.)
The pleasure of writing -- Acacia Road -- My library -- The chase -- Superstition -- The charm of golf -- Goldfish -- Saturday to Monday -- The pond -- A seventeenth-century story -- Our learned friends -- A word for autumn -- A Christmas number -- No flowers by request -- The unfairness of things -- Daffodils -- A household book -- Lunch -- The friend of man -- The diary habit -- Midsummer day -- At the bookstall -- "Who's who" -- A day at Lord's -- By the sea -- Golden fruit -- Signs of character -- Intellectual snobbery -- A question of form -- A slice of fiction -- the label -- The profession -- Smoking as a fine art -- The path to glory -- A problem in ethics -- The happiest half-hours of life -- Natural science -- On going dry -- A misjudged game -- A doubtful character -- Thoughts on thermometers -- For a wet afternoon -- Declined with thanks -- On going into a house -- The ideal author.
Release date is 2004-06-01
Scanned by Charles Aldarondo, text proof read by the volunteers of the Distributed Proofreaders site. Post production formatting by JC Byers
Keywords: English essays